Charged-Higgs effects in a new B ---> D [Tau Nu] differential decay distribution - Nierste, Ulrich; Trine, Stéphanie; Westhoff, Susanne (Arxiv, 2008)
We show that the decay mode B -> D tau nu is competitive with and complementary to B -> tau nu in the search for charged-Higgs effects. Updating the relevant form factors, we find that the differential distribution in the decay chain B -> D nu tau[-> pi nu] excellently discriminates between Standard-Model and charged-Higgs contributions. By measuring the D and pi energies and the angle between the D and pi three-momenta one can determine the effective charged-Higgs coupling including a possible CP-violating phase.